Desintegración familiar, durante el proceso pedagógico virtual para desarrollar destrezas cognitivas, en los alumnos de quinto año de educación general básica, paralelo “A” de la unidad educativa “Roberto Arregui Chauvin” de la provincia Bolívar cantón Guaranda en el año lectivo 2021-2022 - Guaquipana Cayambe, Morayma Beatriz (2022)
A boy that comes from family disintegration doesn't pay the same attention in classes it is affected by the problems that his parents are crossing, and this is a serious lack because the children should not perceive these situations since they don't have the capacity to understand neither of understanding why they pass those things. In the development of the present project it was identified the key actors that should intervene in the cognitive development of the children among these we have the parents who are those that inculcate securities and respect towards other people, mainly they are an important base for the learning and the children's academic and social development. The teachers who are those that impart knowledge are also so that the children acquire them and follow the academic development, they are the fundamental base so that the children develop cognitive dexterities, the expert psychologist of the DECE also plays a paper I/you/he/she cares since she helps the children to understand difficult situations as you/he/she is the family disintegration. Our study universe is conformed of 25 children, 2 teachers, an expert and 25 family parents, to all are carried out an interview with the purpose of to know the grade of knowledge that you/they have about the study topic, and to know if they are fulfilling their lists in the cognitive development of the children. By means of our investigation we find that two children that are going by a family disintegration exist it carries to an extreme, that is to say that their parents are separating, this has generated that these children you desinteresen for the study, the contribution of our investigation helped to that all the academic and social actors are working so that the cognitive development of these children is efficient.